Praktik Pembagian Tellon untuk Pemilik Sawah oleh Petani Tembakau Ditinjau dari Akad Syirkat al-‘Inan di Desa Pademawu Timur - Subroto, Gatot; Suhaimi, Suhaimi; Rifai, Achmad; Wulandari, Ayuni Putri; Maulana, Arief (LP2M IAI Miftahul Ulum Pamekasan, 2023)
The East Pademawu community can be said to be an Islamic society because all its citizens are Muslim. In carrying out economic practices (mu'amalah), quite a few people use sharia contracts. The most popular one is the syirkah contract (Syirkat al-'Inan) with the muza'ra'ah system. In this system, it is often carried out in cooperation in growing tobacco with a Tellon profit sharing system for rice field owners and Tello' Perapat for cultivators. When viewed from the syirkah 'inan, the practices carried out by the people of East Pademawu Village do not violate the provisions of the sharia economic system at all as long as they are carried out with a clear agreement and with the mutual consent of both parties. The approach chosen by the researcher is a qualitative approach which aims to reveal a phenomenon that occurs in the field and is contextual in finding and understanding the practice of distributing Tellon for rice field owners from the perspective of the Syirkah 'Inan contract as part of the sharia economic system.